"If you want to pray to Mercury, wear the garments of a scribe:" kuttāb, udabāʾ, and readers of the Ghāyat al-Ḥakīm in the court of ʿAbd al-Raḥmān III. Issue 2 (4th May 2022) - Udaondo Alegre, Juan
ABSTRACT: This work addresses the question of the intended audience of the Ghāyat al-Ḥakīm, the famous Andalusi treatise on magic, better known by its Latin moniker, Picatrix . I propose that a substantial portion of the Ghāya 's readers were scribes, or kuttāb, in the tenth-century caliphate of Cordova. Many of these scribes were considered udabāʾ ; that is, those who possessed adab, an elusive yet ubiquitous term in Islamic culture. The concept of adab, scribal culture, and magic traveled to al-Andalus in similar ways and at similar times, and they reached their apex in two figures: Ibn Rabbih and al-Qurṭubī. I argue that, in the Ghāya 's spells and rituals, these kuttāb and udabāʾ could find not only a shortcut to acquire abilities vital to their work but also more dubious ways to promote themselves in a difficult political environment. Further, I show that sections of the Ghāya potentially allowed these officials to establish contact with the "supreme scribe, " the personified planet Mercury, who is closely related to the mythical sage Hermes Trismegistus.